AR to GR switch modulates differential TDO2-Kyn-AhR signalling to promote the survival and recurrence of treatment-induced dormant cells in prostate cancer - Sangsang Li; Yifan Zhang; Maoxing Luo; Weiwei Zhou; Yitong Chen; Dinglan Wu; Qiang Wei; Yan Chang; Hailiang Hu (Cell Discovery)
Abstract Cancer cells can be induced to dormancy initially by specific cancer therapies, but can be reactivated for subsequent relapse as therapy-resistant cancer cells. Although the treatment-induced dormancy-to-reactivation switch is an important process in tumour spread and recurrence, little is known about the underlying molecular mechanisms, particularly the metabolic underpinnings. In this study, we demonstrated that the tryptophan catabolism-related tryptophan 2,3-dioxygenase (TDO2) -kynurenine (Kyn) -aryl hydrocarbon receptor (AhR) signalling axis was responsible for both sustaining the survival of dormant prostate cancer cells induced by androgen deprivation therapy (ADT) and promoting the reactivation of dormant cells and their recurrent outgrowth, which facilitated the development of therapeutic resistance by allowing the dormancy-to-reactivation switch. Mechanistically, we found that ADT upregulated the expression of TDO2 to produce Kyn, which activated AhR and maintained the survival of ADT-induced dormant cells. Interestingly, the switch of transcription factors from the androgen receptor (AR) to the glucocorticoid receptor (GR) modulated the persistent expression of TDO2 and promoted the reactivation of dormant cells through the same TDO2-Kyn-AhR signalling axis. Additionally, tumour recurrence following ADT was delayed by pharmacological suppression of TDO2-Kyn-AhR signalling with a TDO2 inhibitor or an AhR inhibitor. In summary, we describe a signalling circuit mediated by tryptophan metabolism for regulating tumour cell dormancy and recurrence and propose TDO2 as a new target for the treatment of androgen-sensitive prostate cancer patients in combination with ADT.